2020
DOI: 10.1101/2020.07.28.225391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The surface of lipid droplets constitutes a barrier for endoplasmic reticulum residential integral membrane spanning proteins

Abstract: Lipid droplets (LDs) constitute globular subcellular structures that mainly serve to store energy in form of neutral lipids, particularly triacylglycerol and steryl esters. LDs are closely associated with the membrane of the endoplasmic reticulum (ER), and are limited by a monolayer membrane of phospholipids harboring a specific set of proteins. Most of these proteins associate with LDs through either an amphipathic helix or a membrane-embedded hairpin motif. Here we address the question whether integral membr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…The ER-LD junctions therefore are strikingly different from other contact sites between organelles delineated by bilayer membranes. This architecture at the ER-LD junction constitutes a barrier for ER residential integral membrane proteins and excludes them from the LD monolayer (Khaddaj et al, 2020). Early cryo electron microscopy (EM) studies have revealed that the cytoplasmic leaflet of the ER membrane is continuous with the LD surface, and freeze fracture EM suggested that the ER membrane forms a cup-like structure that holds the LD in place (Blanchette-Mackie et al, 1995;Robenek et al, 2006).…”
Section: The Endoplasmic Reticulum-lipid Droplet Junction Forms a Unique Interface Between The Endoplasmic Reticulum Lipid Bilayer And LImentioning
confidence: 99%
“…The ER-LD junctions therefore are strikingly different from other contact sites between organelles delineated by bilayer membranes. This architecture at the ER-LD junction constitutes a barrier for ER residential integral membrane proteins and excludes them from the LD monolayer (Khaddaj et al, 2020). Early cryo electron microscopy (EM) studies have revealed that the cytoplasmic leaflet of the ER membrane is continuous with the LD surface, and freeze fracture EM suggested that the ER membrane forms a cup-like structure that holds the LD in place (Blanchette-Mackie et al, 1995;Robenek et al, 2006).…”
Section: The Endoplasmic Reticulum-lipid Droplet Junction Forms a Unique Interface Between The Endoplasmic Reticulum Lipid Bilayer And LImentioning
confidence: 99%